REKAYASA MODEL ALIANSI STRATEGIS AGROINDUSTRI SKALA KECIL (KASUS KLUSTER INDUSTRI TAHU) - KUSNANDAR KUSNANDAR; BEKTI WAHYU UTAMI; SAPJA ANANTANYU (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Development of small scale agro industrial is strategic effort. Through agroindustry there will be constructed the increasing value-added. The aim of this study was to design model strategic alliance for small scale ‘tahu’ agroindustry. Data analysis methods for small scale ‘tahu’ agro industrial strategic alliance developments were: system analysis by need analysis, problem formulation and system identification; system structuration by interpretative structural modeling (ISM); internal and external factor by SWOT analysis; institutional performance analysis. The result of system structuration shows that key components in the objective element are capital access.